Hope for brain health: impacting the life course and society - Dasgupta, Jayashree; Furlano, Joyla A.; Bandler, Zach; Fittipaldi, Sol; Canty, Alison J.; Yasoda-Mohan, Anusha; El-Jaafary, Shaimaa I.; Ucheagwu, Valentine; McGettrick, Grainne; de la Cruz-Góngora, Vanessa; Nguyen, Kim-Huong; Lawlor, Brian; et al. (Frontiers in Psychology, 2023)
Hope is a cognitive process by which an individual can identify their personal goals and develop actionable steps to achieve results. It has the potential to positively impact people's lives by building resilience, and can be meaningfully experienced at both the individual and group level.Despite this significance, there are sizable gaps in our understanding of the neurobiology of hope.In this perspective paper, the authors discuss why further research is needed on hope and its potency to be harnessed in society as a 'tool' to promote brain health across healthy and patient populations. Avenues for future research in hope and the brain are proposed. The authors conclude by identifying strategies for the possible applications of hope in brain health promotion within the areas of technology, arts, media and education."Even if the hopes you started out with are dashed, hope has to be maintained."